Programmable multi-wavelength filter with Mach–Zehnder interferometer embedded in ethanol filled photonic crystal fiber - Zhao, Zhiyong (2014)
We experimentally demonstrated a free spectrum range (FSR) tunable comb filter based on a programmable thermo-controlled Mach–Zehnder interferometer. The device is constructed by sandwiching a length of ethanol-filled photonic crystal fiber between single-mode fibers. A digital thermal printer head is used to facilitate the interference as well as to adjust the phase difference by selectively activating the independent heating elements, thus the FSR can be digitally tuned conveniently. The filter shows a feature of periodic equalized passbands with flat-top steep-edge as well as a high extinction ratio over a very wide range of wavelengths from 1.52 to 1.58 μm.